KRISIS EKOLOGI DALAM CERPEN IKAN KARYA DANANG FEBRIANSYAH - Randa Anggarista (Balai Bahasa Kalimantan Barat, 2020)
This research is a qualitative study using an ecocriticism perspective. The data in this study are form of text that refers to the formulation of problem about the form of ecological crisis in the short story of Ikan, while the data source used is the short story of Ikan by Danang Febriansyah. The instrument in this research is writer who oriented to research the short story of Ikan by Danang Febriasnsyah. The validity test in this study uses semantic validity which is oriented to depth of interpretation process. Data collection techniques in this study were carried out by reading and note-taking techniques. The data analysis techniques used are classification, interpretation, and drawing conclusions. Based on the research results, in the short story of Ikan by Danang Febriansyah, it was found that there was a representation of the ecological crisis in form of damage to the biotic ecosystem and the living things in ecosystem experiencing extinction.